2015
DOI: 10.1002/ar.23277
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Early Neuronal Death in the Olivocochlear System Following Acoustic Overstimulation

Abstract: This study was conducted to examine possible effects of noise trauma on olivocochlear (OC) neurons. Anesthetized rats were exposed to a continuous 10 kHz pure tone at 120 dB sound pressure level for 2 hrs. The effects of treatment were verified by recordings of auditory brainstem response and distortion product otoacoustic emission. Three or 8 days after acoustic trauma, rats received unilateral injections of an aqueous solution of the retrograde neuronal tracer Fluorogold (FG) into the scala tympani to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
2
1
0
Order By: Relevance
“…This morphometric analysis was carried out in retrogradely labeled neurons after injections of FG into the cochlea. Consistently with previous track-tracing studies in rodents [21,44,45], our injections generated retrograde labeling of the three types of olivocochlear neurons: LOC, MOC, and shell neurons. We also obtained a distribution pattern of olivocochlear neurons at the ipsicontralateral and rostrocaudal levels, in the GASH:Sal and control hamsters, which was similar to that reported in other rodents [21,[46][47][48][49].…”
Section: Morphological Alterations In the Olivocochlear Efferent System Of The Gah:salsupporting
confidence: 84%
See 2 more Smart Citations
“…This morphometric analysis was carried out in retrogradely labeled neurons after injections of FG into the cochlea. Consistently with previous track-tracing studies in rodents [21,44,45], our injections generated retrograde labeling of the three types of olivocochlear neurons: LOC, MOC, and shell neurons. We also obtained a distribution pattern of olivocochlear neurons at the ipsicontralateral and rostrocaudal levels, in the GASH:Sal and control hamsters, which was similar to that reported in other rodents [21,[46][47][48][49].…”
Section: Morphological Alterations In the Olivocochlear Efferent System Of The Gah:salsupporting
confidence: 84%
“…This might be explained because deficits in ABRs and DPOAEs do not necessarily involve degeneration of olivocochlear neurons. Supporting this argument, a recent study using ABR and DPOAE tests combined with FG injections in the cochlea indicated that, in acoustic trauma, LOC and MOC neurons remain intact despite hair cell dysfunction [44]. Our statistical comparative analysis of the soma area indicated that the MOC, LOC, and shell neurons of the ipsilateral side were significantly smaller in the GASH:Sal than in controls, as well as MOC neurons of the contralateral side.…”
Section: Morphological Alterations In the Olivocochlear Efferent System Of The Gah:salsupporting
confidence: 71%
See 1 more Smart Citation